BEC Vantage Masterclass. Course Book. - ODriscoll, Nina and Scott-Barrett, Fiona (Oxford Oxford University Press, 2003)
BEC Vantage Masterclass is a complete preparation course for the Business English Certificate Vantage exam for pre-service and in-service learners.
Keywords: Business English